The effect of Borago officinalis on the signaling pathway of the NLRP3 inflammasome complex, TLR4 and some inflammatory cytokines in type II diabetic patients with acute respiratory distress syndrome - Yue, Yanqiu; Jin, Fengbin; Yue, Xiaohui (Cellular and Molecular Biology, 2021)
Acute respiratory distress syndrome (ARDS) is a life-threatening condition in which the lungs become severely inflamed, causing the alveoli to constrict or fill with fluid, which prevents the lungs from functioning properly. This disease becomes more dangerous when it occurs in patients with diabetes. Because of the clinical condition of these patients, it is not possible to treat them with usual medicines. One of the best options for treating these people is to use herbs. Borage (Borago officinalis) is a medicinal herb that, in addition to its anti-inflammatory properties, is also able to control blood sugar. Therefore, in the current study, the effect of borage oil was considered on the signaling pathway of the NLRP3 inflammasome complex, TLR4, and serum levels of inflammatory cytokines (IL-1? and IL-18) in type II diabetic patients with ARDS. For this purpose, 25 diabetic type II patients with ARDS were divided into three groups by ARDS Berlin Definition. Then, after providing the demographic and clinical characteristics of the patients, they were treated with 30 mg/day borage oil for seven days. The expression of NLRP3 and TLR4 genes (by Real-time PCR technique) and serum levels of IL-1? and IL-18 (by ELISA test) were evaluated before and after treatment with borage oil through blood samples taken from patients. The results showed that serum levels of inflammatory cytokines (IL-1? and IL-18), NLRP3 gene, and TLR4 gene were significantly decreased in diabetic type II patients with mild ARDS by treating with borage oil. IL-1? serum level and TLR4 were significantly decreased in diabetic type II patients with moderate ARDS. But there was not any significant decrease or increase in IL-1?, IL-18, NLRP3 gene, and TLR4 gene in diabetic type II patients with severe ARDS after 7 days of treatment with borage oil. According to the obtained results, borage oil can act as a double-edged blade. Thus, in the early and middle stages of ARDS, borage oil can be effective in reducing the inflammasome pathway of inflammation and also reduce blood sugar levels in these diabetic patients. But in the severe stage of ARDS, it not only does not help to treat the ARDS; it also increases systolic and diastolic blood pressure in diabetic patients.